Recent Worldwide Developments in eHealth and mHealth to more Effectively Manage Cancer and other Chronic Diseases – A Systematic Review - Lewis, J.; Ray, P.; Liaw, S.-T. (Yearbook of Medical Informatics, 2016)
Objectives: This paper is a systematic literature review intended to gain an understanding of the most original, excellent, state-of-the-art research in the application of eHealth (including mHealth) in the management of chronic diseases with a focus on cancer over the past two years.Method: This review looks at peer-reviewed papers published between 2013 and 2015 and examines the background and trends in this area. It systematically searched peer-reviewed journals in databases PubMed, Proquest, Cochrane Library, Elsevier, Sage and the Institute of Electrical and Electronic Engineers (IEEE Digital Library) using a set of pre-defined keywords. It then employed an iterative process to filter out less relevant publications.Results: From an initial search return of 1,519,682 results returned, twenty nine of the most relevant peer reviewed articles were identified as most relevant.Conclusions: Based on the results we conclude that innovative eHealth and its subset mHealth initiatives are rapidly emerging as an important means of managing cancer and other chronic diseases. The adoption is following different paths in the developed and developing worlds. Besides governance and regulatory issues, barriers still exist around information management, interoperability and integration. These include medical records available online information for clinicians and consumers on cancer and other chronic diseases, mobile app bundles that can help manage co-morbidities and the capacity of supporting communication technologies.
Keywords: eHealth; mHealth; chronic diseases; cancer; management; self-management; self- care